2019
DOI: 10.3390/met9121306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Bath Nitrocarburizing and Post-Oxidation on Static and Fatigue Behaviours of a Construction Steel

Abstract: Several surface modification technologies are typically applied to improve the mechanical properties of the material surface of structural components subjected to severe conditions of load, wear and chemical erosion of the surface. The nitrocarburizing and post-oxidation heat treatment, also known as quench-polish-quench (QPQ), improves the fatigue, wear and corrosion resistance properties of the material, since it increases the surface hardness and generates surface compressive residual stresses. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Two identical prototypes of the test bench have been manufactured, assembled and validated. In order to test the effectiveness of the realised test benches, dynamic tests were carried out to derive the fatigue properties of a set of commercial precise ground bars made of 39NiCrMo3 tempered steel, a material extensively analysed in the scientific literature (see for instance [10,22,23]). The chemical composition of the tested material, experimentally derived using a Bruker Q4 Tasman spectrometer model 130, is reported in Table 3 and results to be compliant to the nominal values specified in relevant standards [24].…”
Section: Dynamic Validation Of the Test Benchmentioning
confidence: 99%
“…Two identical prototypes of the test bench have been manufactured, assembled and validated. In order to test the effectiveness of the realised test benches, dynamic tests were carried out to derive the fatigue properties of a set of commercial precise ground bars made of 39NiCrMo3 tempered steel, a material extensively analysed in the scientific literature (see for instance [10,22,23]). The chemical composition of the tested material, experimentally derived using a Bruker Q4 Tasman spectrometer model 130, is reported in Table 3 and results to be compliant to the nominal values specified in relevant standards [24].…”
Section: Dynamic Validation Of the Test Benchmentioning
confidence: 99%
“…Twelve research articles have been published in this Special Issue of Metals. The subjects are multidisciplinary, including (i) the effect of microstructural defects on the high and very high cycle fatigue strength of metallic materials [1][2][3][4][5], (ii) probabilistic fatigue prognosis incorporating the size of defects and control volume [2,4,6], (iii) the effects of plasticity, high temperature, and aggressive environment on the fatigue response [7][8][9], (iv) thermo-chemo-mechanical treatments to mitigate the detrimental effect of defects on the fatigue strength [10,11], and (v) non-destructive techniques to detect fatigue critical defects [12].…”
Section: Contributionsmentioning
confidence: 99%
“…The defect is in this case the process-induced surface roughening, whose detrimental effect is overweighed by compressive residual stresses and work hardening. Campagnolo et al [11] researched the effect of nitrocarburizing and post-oxidation of the plain and fatigue strength of a low carbon steel. They found that the surface compressive residual stress field pushes crack initiation below the treated in plain samples.…”
Section: Contributionsmentioning
confidence: 99%
“…[ 9 ] It is widely recognized that higher hardness and residual compressive stress are beneficial to steel parts after QPQ treatment for improving fatigue properties. [ 10,11 ] However, the early spalling of the compound layer would accelerate the initiation and propagation of cracks, then significantly reduce fatigue life under rolling contact load. [ 12 ] The microstructure and properties of the compound layer have a decisive and complex influence mechanism on wear, corrosion, and fatigue behavior [ 13 ] of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The hardness profile of the diffusion layer would be obviously increased due to the appearance of alloy nitrides, [ 13,16 ] and thinner compound layers have been observed when the content of the nitride‐forming elements reaches some certain values. [ 11,16,17 ] It is inevitable that Cr‐nitride (CrN) appears in the compound layer on nitride‐high chromium steels. [ 18,19 ] The effect of the chromium nitride on the mechanical properties of the compound layer seems to be negative.…”
Section: Introductionmentioning
confidence: 99%